Strawberry-tree, blackthorn and rose fruits: detailed characterization in nutrients and phytochemicals with antioxidant properties - Barros, Lillian (2010)
The chemical composition and biological properties of three wild fruits (strawberry-tree berries, sloes and dog rose hips) were evaluated, in order to valorise these products as sources of nutrients and nutraceuticals. The analysed fruits contain very useful bioactive phytochemicals such as phenolics, vitamins (ascorbic acid and tocopherols) and carotenoids. All the samples proved to have antioxidant activity (measured by four different in vitro assays) being more significant for rose fruits (EC50 values lower than 90 lg/ml). The combination of bioactive compounds and rich nutritional composition (high contents in carbohydrates, low contents in fat with the precious contribution of polyunsaturated fatty acids, precursors of omega-3 and omega-6 fatty acids) of the studied wild fruits make them a very special food.